A Retrofit for Geothermal Organic Rankine Cycles based on Concentrated Solar Thermal Systems. (September 2017) - Heberle, Florian; Hofer, Markus; Brüggemann, Dieter
Abstract: In this study, a solar thermal retrofit unit for geothermal ORC power plants is analysed under thermodynamic and technical aspects. For the retrofit, the ORC module is extended by a solar superheater and the additional heat input is realized by parabolic trough collectors. The evaluation of the entire system is based on simulations over the period of one year. Therefore, a case study considering geothermal conditions of the Aydin-Salavatli field in the Büyük Menderes Graben in Turkey is conducted. Quasi-stationary simulations of the system are performed considering off-design behaviour of the power plant components. The calculations are based on hourly climate data. The obtained operational parameter of the ORC and solar-field emphasise the technical feasibility of the selected superheating concept in the context of thermal stability of the working fluid. For the considered solar-field sizes, the annually generated electricity is increased up to 4.5 % compared to the stand-alone geothermal power plant.